Dose-Dependent Cholesterolemic Activity of Tocotrienols and α-Tocopherol - Teik, Khor Hun; Theng , Ng Theng; Rajendran, Raajeswari (Nutrition Society of Malaysia, 2002)
Tocotrienols and tocopherols are isoforms of vitamin E. Vitamin E may exhibit antioxidant, prooxidant and non-antioxidant activities depending upon circumstances. In this study, the effect of tocotrienols and α-tocopherol on the activities of HMG CoA reductase and cholesterol 7 α-hydroxylase was investigated. Pure tocotrienols were isolated from palm fatty acid distillate and pure α-tocopherol was obtained commercially. Guinea pigs were treated with different dosages of tocotrienols and α-tocopherol. After the treatment period, animals were sacrificed and liver microsomes were prepared. HMG CoA reductase and cholesterol 7α-hydroxylase were assayed using tracer techniques. Our results showed that the effects of tocotrienols and α-tocopherol on the activities of both the enzymes were dose-dependent. At low dosages, both tocotrienols and α-tocopherol exhibited an inhibitory effect on both the enzymes. Moreover, tocotrienols were a much stronger inhibitors than α-tocopherol. At high dosages, on the other hand, tocotrienols and α-tocopherol showed opposite effects on the enzymes. While tocotrienols continued to exhibit an inhibitory effect, α-tocopherol actually exhibited a stimulatory effect on both the enzymes. A possible explanation for this observation is suggested.